Adsorption of alkyltrimethylammonium bromide surfactants at the air/water interface - Nguyen, C.; Nguyen, T.; Phan, Chi (Elsevier Ltd, 2017)
© 2016 Elsevier Ltd The dynamic behavior of three trimethylammonium bromide surfactants, C 14 TAB, C 15 TAB and C 16 TAB, was studied by a dynamic modeling framework, which consists of the Ward and Tordai equation and an adsorption isotherm. Three adsorption isotherms, Langmuir, Henry and Freundlich, were used separately. The simplest isotherm, Henry isotherm, could not fit experimental data. Freundlich isotherm can model C 15 TAB and C 16 TAB adsorption, but failed to describe C 14 TAB. On the other hand, Langmuir isotherm was able to model all three surfactants. The results confirmed that the adsorption isotherm is monotonic but non-linear for all surfactants. In the other words, the surfactants have not reached the saturation at the CMC. The results also demonstrated a monotonic correlation between carbon length and adsorption effectiveness of the cationic surfactants. The new insights are important for designing new cationic surfactants.